FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN CAMPAK PADA BALITA DI PUSKESMAS PANTAI CERMIN KECAMATAN TANJUNG PURA KABUPATEN LANGKAT - Siskawati Amri (Universitas Prima Indonesia, 2018)
Measles is a highly contagious acute disease caused by the measles virus usually attacks children with mild to moderate degree . Around 30,000 Indonesian children die each year from complications of measles . In Langkat in the region of the sub-district health centers mirror the coast of Tanjung Pura measles cases found as many as 30 people ( 3.27 % ) / 275 toddlers . Achievement of Universal Child Immunization Village ( UCI ) sub-district health centers mirror the coast of Tanjung Pura Langkat in 2013 by 90 % . Factors associated with the incidence of measles is immunization status of measles and vitamin A. This study aims to determine the factors associated with the incidence of measles in infants in public health centers Mirror Beach Tanjung Pura Langkat 2013. Kind of research is observational analytic by using a case study design control . The population in this study is that written toddler in public health centers Tanjung Pura Langkat year 2012 so much 275 people . Samples of 90 toddlers using the total sample of this study the incidence of measles cases as many as 30 toddlers and 60 control toddler in the ratio 1: 2. The result showed that there was not relationship status for measles immunization with measles incidence in infants p value 0.11, was not relationship association vitamin A with measles incidence in infants p value 0.096. Langkat District Health Office in order to improve the public health promotion Langkat especially in working areas of existing health centers in Langkat Measles Immunization Campaign through the implementation of programs such as measles in children aged 9 months and vitamin A.